2017
DOI: 10.1589/jpts.29.1675
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high intensity laser therapy in the treatment of male with osteopenia or osteoporosis: a randomized placebo-controlled trial

Abstract: [Purpose] To investigate the effect of high intensity laser therapy, alone or combined with exercise on pain, health related quality of life and fall risk in male with osteopenia or osteoporosis. [Subjects and Methods] 100 male patients with osteopenia or osteoporosis participated in the study. They had T-scores ≤−1.5. Patients were randomly assigned into four groups and treated with laser plus exercise, placebo laser plus exercise, laser alone and placebo laser in groups I, II, III, and IV respectively. Laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…16 The studies that demonstrated positive effects of HILT on pain have some common features as follows: patients were monitored over a long period of time (up to 3 months); higher amounts of energy were used with the average power of 3 and 25 W; the patients most commonly did not use other interventions with laser therapy; and the PBM therapy pulsed for at least ten sessions. 39,42,43 HILT was more effective in the management of pain in patients with lumbar disc protrusion, 18 plantar fasciitis, 13 Children with Juvenile rheumatoid arthritis, 42 children with haemophilic arthropathy, 39 males with osteopenia orosteoporosis, 43 and low back pain. 32 Conversely, the studies which did not supporting a positive effect of HILT (low differences in ES) most commonly did not specify the amount of introduced energy or the simultaneous consumption of non-steroid anti-inflammatory drugs, so it was not possible to make a judgment on whether the energy parameters may have contributed to a suboptimal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The studies that demonstrated positive effects of HILT on pain have some common features as follows: patients were monitored over a long period of time (up to 3 months); higher amounts of energy were used with the average power of 3 and 25 W; the patients most commonly did not use other interventions with laser therapy; and the PBM therapy pulsed for at least ten sessions. 39,42,43 HILT was more effective in the management of pain in patients with lumbar disc protrusion, 18 plantar fasciitis, 13 Children with Juvenile rheumatoid arthritis, 42 children with haemophilic arthropathy, 39 males with osteopenia orosteoporosis, 43 and low back pain. 32 Conversely, the studies which did not supporting a positive effect of HILT (low differences in ES) most commonly did not specify the amount of introduced energy or the simultaneous consumption of non-steroid anti-inflammatory drugs, so it was not possible to make a judgment on whether the energy parameters may have contributed to a suboptimal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…42 Also, the best effect in the first group was on plantar fascia 13 and osteopenia. 43 In the second group, the best outcomes have been shown in Juvenile rheumatoid arthritis 42 and chronic back pain patients. 16 The studies that demonstrated positive effects of HILT on pain have some common features as follows: patients were monitored over a long period of time (up to 3 months); higher amounts of energy were used with the average power of 3 and 25 W; the patients most commonly did not use other interventions with laser therapy; and the PBM therapy pulsed for at least ten sessions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HILT can relieve pain in patients with shoulder 9 ) , neck 10 ) and lower back deriders 11 ) , as well as improve the quality of life in knee osteoarthritis patients 12 ) . In addition, some studies reported its efficacy in nerve recovery 13 ) , wound healing 14 ) , decreasing prostaglandin levels in blood 15 ) , bone density 16 ) and reducing adhesions 17 ) . Although numerous studies have investigated the effects of HILT, no systematic review has been conducted to assess its efficacy on foot ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 115 and others 116 reported that HILT was an effective non-surgical intervention for patients with knee osteoarthritis, reducing pain and improving their ability to perform activities of daily living. Alayat et al 117 reported that, in men with osteopenia and osteoporosis, HILT combined with exercise was more effective than exercise alone in reducing pain and improving quality of life after a series of treatments. Kheshie et al 118 and others 119 have reported that HILT is significantly more effective than LLLT in treating chronic osteoarthritis-related pain.…”
Section: Laser Therapymentioning
confidence: 99%